2015
DOI: 10.15386/cjmed-568
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as non-invasive screening biomarkers of colorectal cancer

Abstract: Colorectal cancer is a major cause of cancer-associated deaths in the world. Early detection would be greatly enhanced if accurate and cost-effective diagnostic biomarkers for this disease were accessible. The development of such a blood test will evidently lower the screening costs in regards of colorectal cancer detection. Lately, it has been suggested that microRNA diagnostic biomarkers are feasible new screening methods for colorectal cancer. This review summarizes the diagnostic potential of circulating m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Profiling of miRNAs can give insight as biomarkers for diagnostic or prognostic applications. For example, panels of miRNAs can be used to classify different cancer phenotypes, predict recurrence or response to therapies [ 1 , 12 , 29 31 ]. However, for discovery and clinical application of miRNA-based biomarkers there needs to be optimised and standardised practices for how the RNA is extracted to prevent conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Profiling of miRNAs can give insight as biomarkers for diagnostic or prognostic applications. For example, panels of miRNAs can be used to classify different cancer phenotypes, predict recurrence or response to therapies [ 1 , 12 , 29 31 ]. However, for discovery and clinical application of miRNA-based biomarkers there needs to be optimised and standardised practices for how the RNA is extracted to prevent conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, expression profiles of miRNAs in the plasma and/or serum of cancer patients may reflect the change in miRNA expression in tumor cells ( 42 ). Circulating miRNAs may be a novel class of non-invasive biomarkers for cancer diagnostic and prognostic information ( 43 , 44 ). The differential expression of miR-10a/b in different AML subtypes should be validated in more clinical samples to develop a novel method for subtyping AML according to miRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Within the last decade a number of researchers have demonstrated that long non-coding RNAs (lncRNAs) are stable in blood and have diagnostic potential [ 148 , 149 , 150 , 151 ]. Based on length, ncRNAs are divided into two classes: small non-coding RNAs, whose length is a maximum of 200 nucleotides (i.e., microRNAs (miRNAs), small interfering RNAs (siRNAs), PIWI-interacting RNAs (piRNAs)) [ 152 , 153 ]; and long non-coding RNAs (lncRNAs), which have 200 or more nucleotides and which influence cancer cells through mechanisms such as chromatin remodeling, chromatin interaction, competing endogenous RNAs and natural antisense transcripts [ 154 ].…”
Section: Blood Biomarkersmentioning
confidence: 99%